Keberlakuan Asas Legalitas Terhadap Hukum yang Hidup dalam Masyarakat pada KUHP Baru - Regar Vina Febrina (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The principle of legality is one of the main principles adopted by criminal law. Indonesia has incorporated the principle of legality into the first article of the Criminal Code, which carries the consequence that the imposition of criminal penalties must first be regulated in written law. The reform of criminal law through the New Criminal Code continues to apply the principle of legality in Article 1 and also adds recognition to the laws existing in society that are generally unwritten. The recognition of unwritten laws in the New Criminal Code does not mean shifting the principle of legality and applying the law arbitrarily, but rather a form of realization of the principle of legality in accordance with the characteristics of Indonesian society. The New Criminal Code has provided limits on the application of unwritten laws existing in society, namely if the Criminal Code does not regulate the punishment and must be in accordance with Pancasila, the 1945 Constitution of the Republic of Indonesia, human rights, and general legal principles recognized by the community of nations.